Dot vertigo : - Nolan, Richard L. (John Wiley and Sons, 2001)
To succeed in the years ahead, corporations will need "permeable" structures without boundaries between the corporation and all its stakeholders, argues Harvard Business School professor Nolan. Existing technology can be used to create strategy, not just to solve problems, he emphasizes. Information technology specialists are likely to find this book helpful in pitching their case to and as part of their plan to become senior management. Other managers are likely to be overwhelmed by the level of detail.